A Descriptive Analysis of Corporate Environmental Responsibility in Major League Professional Sport - Martin Barrett; Kyle S. Bunds; Jonathan M. Casper; Michael B. Edwards (Journal of Applied Sports Management, 2019)
This article explores corporate environmentalism across North American major league professional sport through a webpage content analysis of disclosed business practices and programs. The results of the content analysis reify previous academic work, which suggests corporate environmental responsibility in professional sport is varied. Yet, the results also point to an increasingly standardized approach to integrated/operational business practices focusing on materials and resources, and energy and atmosphere, as well as campaign-based programs focusing on corporate social marketing. The findings identify an opportunity for professional team sport organizations to innovate new cause-related marketing and cause promotion programs, and point to a key role for senior leaders in leveraging advanced capabilities to catalyze knowledge development in other business practices and programs. Additionally, by establishing common areas of success, the findings present an opportunity for professional team sport organizations to communicate their environmental successes collectively. Subscribe to JASM
Keywords: CSR; environment; professional sport; resource